THE INTEGRATION OF EDUCATION, SCIENCE, AND INDUSTRY: THE MODEL OF BAUMAN UNIVERSITY - Alexander S. Fadeev; Vladimir N. Gerdy; Valery K. Baltyan; Vladimir G. Fedorov (Высшее образование в России)
The explores the prerequisites of the engineering activities in conditions of the formation of knowledge-based society. Relevance and demand of advanced engineering education, new forms of content and implementation have been specially noted. The article reveals the basic principle of the classical Russian school of engineering polytechnic education based on the integration of education, science and industry, effective interaction and cooperation with industry and research organizations. The example of organization and operation of the branch of the Faculty of National Research Technical University based on the integrated system of education and continuous research and production practice of students has been represented.